DASAR DAN PERTIMBANGAN HAKIM DALAM MENGABULKAN PERMOHONAN PELAKSAKSANAAN PERKAWINAN BEDA AGAMA (STUDI PUTUSAN NO. 622/PDT.P/2018/PN.MKS.) - Hidayah, Nur (UNES Law Review, 2023)
In the provisions of the Marriage Law, there are no clear provisions regarding the arrangement of interfaith marriages, giving rise to a legal vacuum, to carry out marriages of different religious statuses, they must first obtain a stipulation granted by the PN. PN can be granted by the judge. Even though the Marriage Law does not regulate marriage with different religious statuses. The type of research chosen by the author in this study is normative (normative juridical). This relates to reviewing, explaining, and analyzing legal regulations relating to interfaith marriages, by examining legal materials such as a copy of Case Determination No. 622/Pdt.P/2018/PN.Mks regarding Basis for Judge Considerations in Granting Applications for Execution of Different Marriages Religion. Whereas the basis for the Makassar District Court judge in granting the request of the applicant named X (pseudonymized name) of the applicant and the applicant named Y (pseudonymized name) regarding the implementation of marriages of different religions is to prevent the application of smuggling of social and religious values "samen leven" or cohabiting and smuggling applicable laws. Then the judge's consideration was that the wishes of the applicants must be respected as part of human rights according to what was mandated in articles 27 and 29 of the 1945 Constitution and guided by the decision of the Supreme Court of the Republic of Indonesia No: 1400 K/Pdt/1986 dated 20 January 1989.